Focus Group Discussion on Strengthening the Jaranan Jember Arts Organization - Riza Bahtiar Sulistyan; Imanita Septian Rusdianti; Rohmatul Faizah; Moch. Ilham Umarudin; Dian Ramadhani; Tsamrotul Fu'adiyatus Soimi (TGO Journal of Community Development, 2026)
The activity to strengthen the jaranan kepruk jemberan art organization in Jember Regency aims to strengthen traditional art institutions so that they remain relevant and contribute to socio-cultural development. The method used is focus group discussion with stages of planning, implementation, and evaluation as well as data analysis using a qualitative approach. The results of the activity show that strengthening the organization is able to identify institutional needs, strengthen management, increase artist regeneration, and open up opportunities for cooperation with the government and the private sector. The discussion emphasized that the process of strengthening the organization not only improves the internal structure but also strengthens community solidarity and encourages performance innovation. Thus, this activity is a strategic step in maintaining the existence of the art of jaranan kepruk jemberan while expanding its contribution to the people of Jember.